“#I-Am-Engaged”: Conceptualization and First Implementation of a Multi-Actor Participatory, Co-designed Social Media Campaign to Raise Italians Citizens’ Engagement in Preventing the Spread of COVID-19 Virus - Graffigna, Guendalina; Bosio, Caterina; Savarese, Mariarosaria; Barello, Marina; Barello, Serena (Frontiers in Psychology, 2020)
The COVID-19 pandemic forced health authorities around the world to introduce public health measures to contain the risks of contagion. This greatly impacted on citizens’ quality of life, often raising concerns and reactance. There is an ongoing urgent need to promote and sustain behavioral changes and adherence to preventive measures. Based on the theoretical framework of the Patient Health Engagement Model and a participatory co-design process, a social media campaign aimed at improving citizens’ health engagement toward behavioral change for preventing the spread of COVID-19 was promoted in Italy in the early months of the pandemic. In this paper, we describe the methodological process adopted to develop the campaign, its characteristics, and the first results—in terms of audience reach and engagement in its early implementation. The discussion of this grounded-up and citizen-centered approach to social campaign development highlights key ways of promoting learning, engaging citizens, and supporting their participation in the co-production of educational interventions for behavioral change toward preventive actions.